A fistful of euros: Does One-Euro-Job participation lead means-tested benefit recipients into regular jobs and out of unemployment benefit II receipt? - Katrin Hohmeyer; Joachim Wolff (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2007)
In 2005 a major reform of the German means-tested unemployment benefit system came into force. The reform aimed at activating benefit recipients, e.g., by a workfare programme, the so-called One-Euro-Job. This programme was implemented at a large scale. Participants receive their means-tested benefit and a small compensation of usually one to 1.5 EURO per hour worked. Participation typically lasts six months or less. We investigate the impact of One-Euro-Jobs for participants who entered the programme at the start of the year 2005. We apply propensity score matching to estimate the treatment effects on the outcomes regular employment, neither being registered as unemployed nor as job-seeker and no unemployment benefit II receipt. We observe these outcomes for about two years after programme start. The locking-in effects are small. Moreover, 20 months after programme there is a significant but small positive impact on the employment rate of female but not male participants. During the first two years after programme start, participation does not contribute to avoiding unemployment benefit II receipt. Our results imply that there is some effect heterogeneity: Participation reduces the employment rate of participants younger than 25 years, but raises it for some older participant groups. It is ineffective for participants who were recently employed, while it is effective for participants who lost their last contributory job between 1992 and 2000.
Keywords: C13; H43; J68; 330; Propensity score matching; evaluation of active labour market policy; workfare; means-tested benefit recipients